PXR variants: the impact on drug metabolism and therapeutic responses - C. Trent Brewer; Taosheng Chen (Elsevier, 2016)
The pregnane X receptor (PXR) plays an important and diverse role in mediating xenobiotic induction of drug-metabolizing enzymes and transporters. Several protein isoforms of PXR exist, and they have differential transcriptional activity upon target genes; transcript variants 3 (PXR3) and 4 (PXR4) do not induce target gene expression, whereas transcript variants 1 (PXR1) and 2 (PXR2) respond to agonist by activating target gene expression. PXR protein variants also display differences in protein-protein interactions; PXR1 interacts with p53, whereas PXR3 does not. Furthermore, the transcript variants of PXR that encode these protein isoforms are differentially regulated by methylation and deletions in the respective promoters of the variants, and their expression differs in various human cancers and also in cancerous tissue compared to adjacent normal tissues. PXR1 and PXR4 mRNA are downregulated by methylation in cancerous tissue and have divergent effects on cellular proliferation when ectopically overexpressed. Additional detailed and comparative mechanistic studies are required to predict the effect of PXR transcript variant expression on carcinogenesis, therapeutic response, and the development of toxicity.